Pertumbuhan Rumput Laut (Eucheuma cottoni) Menggunakan Metode Penanaman Berbeda Dengan Sistem Kantong Di Perairan Pantai Pandawa, Badung, Bali - Akbar Akbar; Ni Luh Watiniasih; Ayu Putu Wiweka Krisna Dewi (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2020)
This study aims to determine the level of effectiveness and efficiency of seaweed growth grown in bags with different methods. This research was conducted in the village of Kutuh in the waters of Pandawa Beach in December 2019 to January 2020, by taking data once a week for 6 weeks. This research is experimental using Completely Randomized Design (CRD) which consists of two different treatments namely A (Apart in a bag) and B (Bound in a bag). The results showed that the growth pattern of seaweed in treatments A and B was almost the same. Treatment A added weight of seaweed in the 6th week reached 638,444 grams and treatment B reached 637,333 grams. Specific Growth (SGR) Treatment A was 4,409% while treatment B was 4,413%. The results of interview of 10 respondents who were interviewed 70% of farmers prefer to remain a seaweed cultivator and another 30% choose to switch professions as a provider of tourism services. Of the 70% percentage can be said that 100% of farmers prefer Treatment A as a method that can be applied. The measurement of water quality during the study were temperature range between 28,5 - 33 0C, depth ranged from 0,47 – 1,5 m, pH ranged from 7-7.7, salinity ranged from 26,3 - 34 ppt, DO ranged from 5,1 – 7,9 mg / l, nitral ranged between 1,87 – 2,04 mg / l, phosphate ranges from 0,25 – 0,33 mg / l. The value of water quality is still in the optimal range for seaweed growth.